1987
DOI: 10.3109/00365528708991870
|View full text |Cite
|
Sign up to set email alerts
|

24-H Comparison between pH Values of Continuous Intraluminal Recording and Simultaneous Gastric Aspiration

Abstract: This study was undertaken to show whether the correlation between pH values indicated by an intraluminal pH electrode and those simultaneously recorded for gastric aspirates is not only linear but also proportional, so that the two measurement techniques can be considered alternative. A 24-h intragastric pH-monitoring with an antimony electrode, to which a nasogastric tube for hourly aspiration of gastric juice was closely attached, was performed on 20 duodenal ulcer patients. Our data show that the slope of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 4 publications
0
14
1
Order By: Relevance
“…In fact, various kinds of smoothing modalities have already been used not only for graph purposes [19], but also for statistical analysis [20][21][22], In the latter cases raw experimental data were also replaced with smoothed data for calculating the variables of interest. Therefore the at tempts at smoothing out the abrupt short lived changes in gastric pH appear to be use ful in the clinical setting and this is con firmed by the fact that both the singly smoothing and the combined smoothing/filtering techniques used in our study allowed us to obtain better results than those we pub lished previously [11], which were however satisfactory. The combination of Fourier's filtration with the moving averages smoothed data has improved all the various regression analysis parameters and greatly reduced the scattering of pairs, which was present in our original unmodified analysis.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In fact, various kinds of smoothing modalities have already been used not only for graph purposes [19], but also for statistical analysis [20][21][22], In the latter cases raw experimental data were also replaced with smoothed data for calculating the variables of interest. Therefore the at tempts at smoothing out the abrupt short lived changes in gastric pH appear to be use ful in the clinical setting and this is con firmed by the fact that both the singly smoothing and the combined smoothing/filtering techniques used in our study allowed us to obtain better results than those we pub lished previously [11], which were however satisfactory. The combination of Fourier's filtration with the moving averages smoothed data has improved all the various regression analysis parameters and greatly reduced the scattering of pairs, which was present in our original unmodified analysis.…”
Section: Discussioncontrasting
confidence: 54%
“…In a recent investigation [11] we showed that good correlation exists between hourly pH values measured simultaneously in the stomach with an antimony minielec trode and in gastric aspirates.…”
Section: Introductionmentioning
confidence: 99%
“…In direct comparative studies it was proven that although with the gastric aspira tion method only 24 pH values were re corded there were no gross differences in the acidity profiles when compared to the com bined glass electrode which registers thou sands of pH values [34,35] (table 2). (table 3) When compared to the electrode the aspi ration method is at least equally potent in establishing 24-hour pH profiles.…”
Section: Advantages Of the Aspiration Methodsmentioning
confidence: 99%
“…Validation studies of this technique have been carried out by various groups with good correlation reported between the two tech niques [8][9][10], These studies correlated the data point for aspiration with pH electrode recordings taken over the time of aspiration. This may not necessarily be valid for a com parison of data reported in trials of acid sup pression using the pH electrode only, as in these studies the mean or median of the whole hour of recording is usually reported [5,6], Although gastric pH should be constant throughout the stomach [11], consistent elec trode placement is somewhat more difficult than with a nasogastric tube and fluoroscopy may be needed.…”
Section: Introductionmentioning
confidence: 99%